2018
DOI: 10.3390/s18030829
|View full text |Cite
|
Sign up to set email alerts
|

Using Bi-Seasonal WorldView-2 Multi-Spectral Data and Supervised Random Forest Classification to Map Coastal Plant Communities in Everglades National Park

Abstract: Coastal plant communities are being transformed or lost because of sea level rise (SLR) and land-use change. In conjunction with SLR, the Florida Everglades ecosystem has undergone large-scale drainage and restoration, altering coastal vegetation throughout south Florida. To understand how coastal plant communities are changing over time, accurate mapping techniques are needed that can define plant communities at a fine-enough resolution to detect fine-scale changes. We explored using bi-seasonal versus single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…In a similar way, the addition of summer images to the previously used autumn-season images provided 12.8% higher accuracy for the ultra-resolution suite and 13.2% higher accuracy for the very high-resolution suite in this research across three cool temperate ecosystem sites. Wendelberger et al [109] also explored bi-seasonal versus single-season WorldView-2 images to map three mangrove and four adjacent plant communities and found that bi-seasonal images were more effective than single-season to differentiate all communities of interest, in line with this research carried out in three mountainous ecosystems. Ferreira et al [37] utilized WorldView-3 images acquired in the dry and wet seasons and emphasized the usage of seasonal images for tree species discrimination in semi-deciduous forests.…”
Section: Discussionsupporting
confidence: 54%
“…In a similar way, the addition of summer images to the previously used autumn-season images provided 12.8% higher accuracy for the ultra-resolution suite and 13.2% higher accuracy for the very high-resolution suite in this research across three cool temperate ecosystem sites. Wendelberger et al [109] also explored bi-seasonal versus single-season WorldView-2 images to map three mangrove and four adjacent plant communities and found that bi-seasonal images were more effective than single-season to differentiate all communities of interest, in line with this research carried out in three mountainous ecosystems. Ferreira et al [37] utilized WorldView-3 images acquired in the dry and wet seasons and emphasized the usage of seasonal images for tree species discrimination in semi-deciduous forests.…”
Section: Discussionsupporting
confidence: 54%
“…They reported overall accuracies of 83% (Landsat-8) and 86% (SPOT-6). [ 73 ] used RF and Worldview-2 for a bi-seasonal analysis of seven woody plants. The authors recorded woody plant species from 4-m 2 plots in a Subtropical savanna forest covering 71 km 2 and reported overall accuracy of 86%.…”
Section: Remote Sensing Of Savanna Woody Plant Species Diversity Usin...mentioning
confidence: 99%
“…Herrero et al [35] found out that the RF classifier was the best method for distinguishing African savannas in Chobe National Park in Botswana, which has a highly heterogeneous mixture of woody and herbaceous vegetation. Wendelberger et al [53] observed that bi-seasonal data were more effective than single-season data to differentiate coastal plant communities in Everglades National Park.…”
Section: Lulc and Vegetation Community Classificationmentioning
confidence: 99%
“…A major challenge is how to provide valuable insights into site-specific PA management through the interpretation of remote sensing images rather than just describe the symptoms [42]. Remote sensing has the potential to identify the complex drivers of change in human-nature coupled systems, which is generally induced by human activities (including human settlements [66], urbanization [31], excessive tourism [35], mining [85], logging [67], agriculture expansion [37], grazing [127], and hunting [124]) and natural disturbances (including climate variabilities such as droughts [101] and sea-level rise [53], as well as species invasions [118] and megafauna roaming [61,98]). The analysis of remote sensing data alone has limits for discovering accurate and reliable information on the driving forces that threaten ecosystems and for proposing countermeasures for PAs.…”
Section: Discovering the Driving Forces And Providing Measures For Pa...mentioning
confidence: 99%